Exercise-induced mitochondrial biogenesis in muscle 2 - Hood, David (Henry Stewart Talks, 2018)
Calcium signaling in mitochondrial biogenesis, The role of PGC-1alpha, PGC-1alpha expression and exercise, Regulators of the expression of PGC-1alpha, Overview of mitochondrial assembly, Overview of mitochondrial assembly, Activity-induced changes in protein import, Aging muscle and exercise adaptations, The mitochondrial life cycle, Lysosomal adaptations, Exercise is mitochondrial medicine